Survival and Clinicopathological Features of Cervical Carcinoma Patients with Radiation Therapy - Yahya Irwanto; Aliesya Patricia Wulandari; Ineke Permatasari; Ainun Ganisia; Lilik Zuhriyah; I Wayan Agung Indrawan; Sutrisno . (Medical Laboratory Technology Journal, 2022)
Cervical cancer has a high incidence with a low survival rate. The clinicopathological profile and risk factors cause this. Most cervical cancer sufferers are late in realizing this, contributing to the severity suffered. Radiation has a very important role because it is a therapy that can be done in cervical cancer patients who have experienced an advanced level of severity. This study aims to determine the survival and influence of the clinicopathological and risk factors of radiation patients as a consideration in selecting effective therapy to increase the survival rate of cervical cancer patients. The benefit of this research is to help evaluate cervical cancer management procedures with radiation therapy applied in many hospitals in Indonesia to increase the success of therapy for cervical cancer. An analytical observational study with a retrospective cohort type using medical record data with samples of all patients diagnosed with cervical cancer who received radiation therapy from January to December 2017. Samples in this study were 111 patients. This study revealed that the five-year survival rate of cervical cancer patients was only 53.1%. There was an influence on the clinicopathological stage (p<0.000), histopathology (p<0.000), lymph node status (p<0.000), degree of differentiation (p<0.001), and risk factors for age (p<0.038), parity (p<0.001), education (0.022), marital status (0.001), contraceptive use (p<0.000), and BMI (p<0.000) which resulted in a log-rank p-value <0.05, so it was concluded that there was an effect between these variables on cervical carcinoma survival rate. Multivariate, it was found that radiation, histopathology, lymph node status, contraception, and BMI had a significant effect (p<0.005) on the survival rate of cervical cancer patients. The results of this study indicate that the survival rate of cervical cancer patients is still low, and there is a clinicopathological and risk factors that influence the survival rate of cervical cancer patients.